Etika Politik dalam Bayang-Bayang Pragmatisme: Studi Kasus Koalisi “Gemuk” dan Dampaknya Terhadap Fungsi Oposisi - Munandar, Agus; Maiwan, Mohammad; Camelyn Sinaga, Irene (Jurnal Ragam Pengabdian, 2026)
This study examines the phenomenon of oversized coalitions in Indonesia’s multiparty political system and their implications for the function of opposition in democracy. The main focus of this research is to analyze how political pragmatism influences the formation of broad governing coalitions and its impact on political ethics and the quality of democracy. The phenomenon of oversized coalitions reflects the tendency of political parties to prioritize strategic interests and access to power over ideological consistency and political ethical principles. This research employs a qualitative method with a descriptive-analytical approach. Data were collected through library research and documentation from various sources, including books, scientific journals, reports from international institutions, and relevant political documents. The analysis was conducted by examining the relationship between political pragmatism, the formation of oversized coalitions, the weakening of opposition, and the decline in democratic quality. The findings indicate that oversized coalitions are capable of creating political stability and strengthening governmental effectiveness in the short term. However, on the other hand, such conditions weaken the function of opposition as a mechanism of checks and balances. The dominance of large coalitions reduces oversight of the government, decreases the quality of political competition, and increases tendencies toward party cartelization and elite political consolidation. This phenomenon also contributes to democratic backsliding, characterized by declining accountability, transparency, and the quality of public deliberation in democracy. This study concludes that oversized coalitions are not merely a matter of political strategy, but also an issue of political ethics that affects the sustainability of democracy. Therefore, strengthening the role of opposition, revitalizing political ethics, and reinforcing mechanisms of power oversight are necessary to ensure that democracy functions substantively rather than merely procedurally..